Volume 1: Fora, Parts A, B, C, and D 2003
DOI: 10.1115/fedsm2003-45397
|View full text |Cite
|
Sign up to set email alerts
|

CFD Validation for a Marine Propeller Using an Unstructured Mesh Based RANS Method

Abstract: Results of computational fluid dynamics validation for flow around a marine propeller are presented. Computations were performed for various advance ratios following experimental conditions. The objectives of the study are to propose and verify a hybrid mesh generation strategy, and to validate computational results against experimental data with advanced computational fluid dynamics tools. Computational results for both global and local flow quantities are discussed and compared with experimental data. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This has led to unstructured grids being favoured since these can easily handle complex geometries and the clustering of grid cells in regions of the fl ow where large parameter gradients occur. Rhee and Joshi (2003) analysed a fi ve-bladed c.p.p. propeller in open water conditions using hybrid unstructured meshes in which they used prismatic cells in the boundary layer with a system of tetrahedral cells fi lling in the remainder of the computational domain far from the solid boundaries.…”
Section: Computational Fl Uid Dynamics Methodsmentioning
confidence: 99%
“…This has led to unstructured grids being favoured since these can easily handle complex geometries and the clustering of grid cells in regions of the fl ow where large parameter gradients occur. Rhee and Joshi (2003) analysed a fi ve-bladed c.p.p. propeller in open water conditions using hybrid unstructured meshes in which they used prismatic cells in the boundary layer with a system of tetrahedral cells fi lling in the remainder of the computational domain far from the solid boundaries.…”
Section: Computational Fl Uid Dynamics Methodsmentioning
confidence: 99%
“…Felli et al [9] measured wake field and pressure fluctuation downstream of the propeller to investigate the correlation of the velocity and pressure signal. On the other hand, numerical simulations using computational fluid dynamics (CFD) based on Reynolds averaged Navier−Stokes (RANS) equations were performed by Rhee and Joshi [10], Di Felice et al [11], Arikan et al [12], Wang and Walters [13], Baek et al [14], and Kinaci and Gokce [15] to study the characteristics of propeller wake.…”
Section: Introductionmentioning
confidence: 99%
“…CFD can significantly predict the thrust and torque of the propeller under the influence of cavitation. For the steady simulation, the domain geometry was the same as that of Rhee and Joshi (2003) where only one blade was simulated. But for the unsteady domain, a complete propeller was simulated with an infinite cylinder in the middle of the blade to serve as a hub.…”
Section: Literature Surveymentioning
confidence: 99%
“…The result showed that CMBET was only true to experimental values if the fluid-flow was in 2D, but for CFD the performance of the propeller can still be predicted, with certain degrees of agreement with the experiment, even though the flow is 3 dimensional. Rhee and Joshi (2003) conducted a study to validate the flow around a marine propeller using unstructured mesh based on the Navier-Stokes solver. The study was conducted based on the P5168 propeller type with a diameter of 0.402 metres, which were designed at the David Taylor Model Basin.…”
Section: Literature Surveymentioning
confidence: 99%